Antagonists of PD-1 and PD-L1 in Cancer Treatment - Lipson, Evan J; Forde, Patrick M; Hammers, Hans-Joerg; Emens, Leisha A; Taube, Janis M; Topalian, Suzanne L (Seminars in oncology, 2015)
The PD-1 pathway, comprising the immune cell co-receptor Programmed Death 1 (PD-1) and its ligands, PD-L1 (B7-H1) and PD-L2 (B7-DC), mediates local immunosuppression in the tumor microenvironment. Drugs designed to block PD-1 or PD-L1 "release the brakes" on anti-tumor immunity and have demonstrated clinical activity in several types of advanced cancers, validating this pathway as a target for cancer therapy. Two such drugs have recently been approved to treat melanoma and lung cancers, and regulatory approvals in first- and second-line settings for additional cancer types are anticipated. The manageable safety profile of PD-1/PD-L1 blocking drugs identifies them as suitable for outpatient administration and the development of combinatorial therapies. Ongoing studies aim to identify biomarkers to guide patient selection, which would further improve the risk:benefit ratio for these drugs.